THE INFLUENCE OF METACOGNITIVE STRATEGIES TOWARDS STUDENTS’ READING COMPREHENSION - Tasya Putri Nur Annisa; Nani Ronsani Thamrin; Erwin Oktoma (UIBU, 2023)
The purpose of this research is to ascertain the impact of metacognitive methods on students' reading comprehension as well as the attitudes of students about their usage. According to(Navarro, 2021), metacognition is the awareness of and control over one's own thinking and learning processes. Quantitative research is carried out using an experimental research design. Tests and questionnaires were employed by researchers as data collection tools. In this research, two classes—X.6 (Control Class) and X.7 (Experimental Class)—were chosen using cluster random sampling. According to the findings, the experimental group's average post-test score was 83.29, whereas the control group's was 78.57. The independent sample t-test was shown to have a lower (two-tailed) significance of 0.010 (0.010 0.05). Then, in the control class, 0.010 (0.010 0.05) is shown. As a result, Ho is considered unacceptable but Ha is welcomed. Conclusion: Students' reading comprehension is impacted by metacognitive tactics used in reading instruction.In addition, the researcher also got the results from the questionnaire data, the majority of experimental class students agreed and strongly agreed on the three items given on the affective, behavioral and cognitive aspects. It can be assumed that most of the experimental class students were influenced by Metacognitive Strategies in improving reading comprehension